Derived carbon composite material of nitrogen-doped tetra-metal MOFs (Metal-Organic Frameworks) and preparation method thereof
By preparing nitrogen-doped tetrametal MOFs-derived carbon composites, the problem of poor adsorption effect of existing materials on non-polar VOCs is solved, efficient adsorption and stability are achieved, and suitable for high-air air filtration.
Patent Information
- Application Number
- CN202510434632.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-08
- Publication Date
- 2025-07-04
AI Technical Summary
The existing adsorption materials have poor adsorption effect on non-polar VOCs such as benzene, especially under low concentration conditions, and the existing composite materials are not suitable for high air volume air filtration.
The Fe-Co-Ce-Zr tetrametal MOFs material was prepared by one-step hydrothermal method. After nitrogen doping and plasma treatment, a nitrogen-doped tetrametal MOFs-derived carbon composite material was formed, with a three-dimensional flower-like nano-microsphere structure and rich pores, enhancing the gravity of π-π bonds and hydrophilic functional groups.
It significantly improves the adsorption effect of low-concentration VOCs, has high specific surface area and good thermal stability, is suitable for large-scale production and is low-cost.
Smart Images

Figure CN120242983A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorption materials, and particularly relates to a nitrogen-doped four-metal MOFs-derived carbon composite material and a preparation method thereof. Background Art
[0002] VOCs refers to volatile organic compounds. VOCs are prone to volatilization at room temperature and have characteristics such as toxicity, irritation, teratogenicity, and carcinogenicity, seriously threatening human health. In recent years, with the rapid development of industrialization, VOCs have been widely emitted in various industrial processes. Among them, benzene is one of the most dangerous VOCs and can enter the human body through respiration or skin contact, leading to acute or chronic benzene poisoning. Currently, the main methods for removing benzene include catalytic conversion, condensation, adsorption technology, etc. Among various benzene treatment technologies, adsorption technology has the advantages of high efficiency and energy conservation in treating low-concentration VOCs. Therefore, developing an efficient VOCs adsorption material is particularly important for the economic regulation of industrial VOCs.
[0003] At present, adsorption materials include activated carbon, MOFs, ion exchange resins, zeolites and other materials. Among them, MOFs have attracted extensive attention due to their large specific surface area, adjustable structure and numerous active sites. The literature [Separation and Purification Technology 289 (2022) 120784] reported a kind of hierarchical porous MIL-101 material with high adsorption performance for polar gases. Utilizing the ultra-high specific surface area, developed pore structure, adjustable pore size and abundant unsaturated metal sites of MIL-101 material, it has a very high adsorption effect on polar VOCs gases. However, due to the presence of polar ligands and metal nodes in MIL-101, its adsorption capacity for non-polar benzene is poor. Especially under low-concentration conditions, benzene molecules cannot accumulate on the mesopores of MIL-101 due to the repulsive force between them, which further reduces the adsorption effect of this material on non-polar benzene molecules. Patent 201811396279.4 discloses a graphene oxide modified activated carbon and its preparation method. A water dispersion of graphene oxide is prepared by mixing graphene oxide, additives, coupling agents and water; then granular activated carbon is immersed in the water dispersion of graphene oxide, and graphene oxide modified activated carbon is prepared through high-speed stirring and heating reaction. Although this activated carbon improves the filtering efficiency for heavy metal ions and polar organic substances, it is mainly applied to various water purification products. Patent 201811318102.2 discloses a preparation method and application of an aluminum-based metal-organic framework @ activated carbon composite material. This invention utilizes the pore structure of activated carbon itself and the oxygen-containing functional groups on the surface and the crystallization process of MOFs material to generate a new crystal form between activated carbon and MOFs crystal units and form new pores. The composite material prepared by this method has a large specific surface area and has more excellent performance in adsorbing and removing VOCs compared with single MOFs and activated carbon. This invention is aimed at powdered activated carbon and cannot be used for large-airflow air filtration either. Therefore, it is necessary to develop a VOCs adsorption material with high adsorption efficiency, environmental friendliness and simple process for VOCs gases.
[0004] The present invention overcomes the deficiencies of the prior art and prepares a nitrogen-doped four-metal MOFs-derived carbon composite material and its preparation method. The nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-derived carbon composite material treated by plasma is used for adsorbing low-concentration VOCs gases. Summary of the Invention
[0005] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a nitrogen-doped four-metal MOFs-derived carbon composite material and its preparation method.
[0006] A preparation method of a nitrogen-doped four-metal MOFs-derived carbon composite material includes the following steps:
[0007] S1: Preparation of Fe-Co-Ce-Zr four-metal MOFs material
[0008] S1.1: Mix DMF, absolute ethanol and water to make a DMF / ethanol / water mixed solution, then dissolve FeCl2·4H2O, CoCl2·6H2O, Ce(NO3)3·6H2O, Zr(NO3)4 and terephthalic acid in the DMF / ethanol / water mixed solution, stir and pour it into a reaction kettle, seal the reaction. After the reaction is completed and the reaction kettle is naturally cooled to room temperature, take out the product in the inner liner, wash and dry it to obtain the Fe-Co-Ce-Zr four-metal MOFs material;
[0009] S2: Preparation of nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material
[0010] Mix urea and the Fe-Co-Ce-Zr four-metal MOFs material synthesized in step S1 evenly in ultrapure water to obtain a mixture. The mixture is filtered and rinsed in an ethanol solution, and then heated and carbonized in an N2 atmosphere. After the obtained powder is naturally cooled to room temperature, a nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material is obtained;
[0011] S3: Plasma treatment
[0012] Place the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material in a plasma reactor, use O2 / H2O as the working gas, and under the conditions of a discharge frequency of 15 - 30 kHz, a discharge voltage of 15 - 20 kV, and a discharge time of 2 - 10 min, use plasma to treat the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C to obtain a nitrogen-doped four-metal MOFs-derived carbon composite material.
[0013] Furthermore, the preparation of the Fe-Co-Ce-Zr four-metal MOFs material in step S1 includes the following steps:
[0014] S1.1: Stir and mix 32 - 45 parts by mass of DMF, 10 - 15 parts by mass of absolute ethanol and 10 - 15 parts by mass of water evenly to make a DMF / ethanol / water mixed solution;
[0015] S1.2: Dissolve 1 - 1.2 parts by mass of FeCl2·4H2O, 1.2 - 2.2 parts by mass of CoCl2·6H2O, 2.1 - 2.5 parts by mass of Ce(NO3)3·6H2O, 2.15 - 2.6 parts by mass of Zr(NO3)4 and 0.6 - 0.8 parts by mass of terephthalic acid in a mixed solution of DMF / ethanol / water, stir in a magnetic stirrer for 60 - 80 min, pour it into the inner liner of a polytetrafluoroethylene reaction kettle, seal the reaction kettle and place it in an oven at 125 - 150 °C for reaction for 10 - 12 h;
[0016] S1.3: After the reaction is completed and the reaction kettle is naturally cooled to room temperature, take out the product in the inner liner, wash it 2 - 3 times with absolute ethanol and deionized water, and dry it at 80 - 120 °C for 4 - 6 h to obtain the Fe-Co-Ce-Zr four-metal MOFs material.
[0017] Furthermore, the preparation of the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material in step S2 includes the following steps:
[0018] S2.1: Mix urea and the Fe-Co-Ce-Zr four-metal MOFs material synthesized in step S1 evenly in ultrapure water. The mass ratio of urea, Fe-Co-Ce-Zr four-metal MOFs material, and ultrapure water is 1:(5 - 7):(15 - 30), and stir at a speed of 50 - 60 r / min for 2 - 3 h to obtain a mixture;
[0019] S2.2: Filter and rinse the mixture in an ethanol solution, repeat 3 - 4 times, then heat it to 500 - 900 °C in an N2 atmosphere and keep the temperature for carbonization for 1 - 3 h. After the obtained powder is naturally cooled to room temperature, the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material is obtained.
[0020] Furthermore, the concentration of the ethanol solution in step S2.2 is 70 - 95 wt%.
[0021] Furthermore, the heating rate of heating in an N2 atmosphere in step S2.2 is 5 - 7 °C / min.
[0022] Furthermore, in step S3, the flow rate of O2 in the plasma reactor is 50 - 500 sccm, and the flow rate of H2O is 10 - 100 sccm.
[0023] A nitrogen-doped four-metal MOFs-derived carbon composite material is prepared by the preparation method of the above-mentioned nitrogen-doped four-metal MOFs-derived carbon composite material.
[0024] Compared with the prior art, the present invention has at least the following beneficial effects:
[0025] 1. The present invention prepares a four-metal MOF material by a one-step hydrothermal method using four metals (Fe-Co-Ce-Zr) and an organic ligand (terephthalic acid), and modifies the MOF by nitrogen doping, followed by carbonization + plasma treatment to obtain a composite material. This material has a three-dimensional flower-like nanospherical structure, and its regular and ordered morphology provides a large specific surface area and a rich pore structure, thus providing more adsorption sites for VOCs molecules; after nitrogen doping, the nitrogen atoms can reduce the π-orbital electron density more than the original carbon atoms from graphite carbon, thereby reducing the π-electron repulsion between graphite nitrogen and benzene and significantly enhancing the π-π bond attraction; plasma treatment can increase hydrophilic functional groups such as carboxyl and hydroxyl groups on the material surface, which have hydrogen bond interactions with VOCs (such as benzene), greatly improving the efficient adsorption of low-concentration VOCs gases.
[0026] 2. A plasma-treated nitrogen-doped Fe-Co-Ce-Zr four-metal MOF-derived carbon composite material prepared by the present invention has good adsorption effect on low-concentration VOCs, the optimal carbonization temperature is 700 °C, the mass adsorption ratio is 10.21%, it has a stable structure, good thermal stability, and good regeneration performance. Moreover, the preparation process is simple, the cost is low, and it is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings incorporated herein and constituting a part of the specification illustrate embodiments of the present disclosure and, together with the specification, are further used to explain the principles of the present disclosure and enable those skilled in the relevant art to implement and use the present disclosure.
[0028] Figure 1 It is a flowchart of a preparation method of a nitrogen-doped four-metal MOF-derived carbon composite material adopted in an embodiment of the present invention.
[0029] Figure 2 It is a bar chart of the benzene cyclic adsorption capacity of Example 1 and Comparative Examples 1-2 of the present invention.
[0030] Figure 3 It is an adsorption-desorption diagram of the materials of Example 1 and Comparative Examples 1-2 of the present invention.
[0031] Figure 4 It is a TGA diagram of the materials of Example 1 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0032] The following will describe in detail a nitrogen-doped four-metal MOFs-derived carbon composite material and its preparation method provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it should be noted here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments. For some well-known technologies, those skilled in the art can also adopt other alternative methods for implementation; moreover, the accompanying drawings are only for more specifically describing the embodiments and are not intended to specifically limit the present invention.
[0033] Example 1:
[0034] A preparation method of a nitrogen-doped four-metal MOFs-derived carbon composite material, as Figure 1 shown, includes the following steps:
[0035] S1: Preparation of Fe-Co-Ce-Zr four-metal MOFs material
[0036] S1.1: Stir and mix 45 g of DMF, 10 g of absolute ethanol, and 10 g of water evenly to make a DMF / ethanol / water mixed solution;
[0037] S1.2: Dissolve 1 g of FeCl2·4H2O, 1.2 g of CoCl2·6H2O, 2.18 g of Ce(NO3)3·6H2O in parts by mass, 2.15 g of Zr(NO3)4, and 0.64 g of terephthalic acid in the DMF / ethanol / water mixed solution, stir in a magnetic stirrer for 60 min, pour it into the inner liner of a polytetrafluoroethylene reaction kettle, seal the reaction kettle, and place it in an oven at 135 °C for reaction for 12 h;
[0038] S1.3: After the reaction is completed, when the reaction kettle cools naturally to room temperature, take out the product in the inner liner, wash it 2 times with absolute ethanol and deionized water, and dry it at 100 °C for 4 h to obtain the Fe-Co-Ce-Zr four-metal MOFs material.
[0039] S2: Preparation of nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material
[0040] S2.1: Mix urea and the Fe-Co-Ce-Zr four-metal MOFs material synthesized in step S1 evenly in ultrapure water. The mass ratio of urea, Fe-Co-Ce-Zr four-metal MOFs material, and ultrapure water is 1:5:20, and stir at a speed of 50 r / min for 2 h to obtain a mixture;
[0041] S2.2: Filter and rinse the mixture in a 70 wt% ethanol solution 4 times, then heat it to 500 °C at a heating rate of 5 °C / min in a N2 atmosphere, keep the temperature for carbonization for 3 h, and naturally cool the obtained powder to room temperature to obtain the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material.
[0042] S3: Plasma treatment
[0043] Place the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material in a plasma reactor, using O2 / H2O as the working gas. The flow rate of O2 in the plasma reactor is 50 sccm, and the flow rate of H2O is 50 sccm. Under the conditions of a discharge frequency of 20 kHz, a discharge voltage of 15 kV, and a discharge time of 5 min, use plasma to treat the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C to obtain a derivative carbon composite material of nitrogen-doped four-metal MOFs.
[0044] Example 2:
[0045] A preparation method of a derivative carbon composite material of nitrogen-doped four-metal MOFs, as Figure 1 shown, includes the following steps:
[0046] S1: Preparation of Fe-Co-Ce-Zr four-metal MOFs material
[0047] S1.1: Stir and mix 45 g of DMF, 10 g of absolute ethanol, and 10 g of water evenly to make a DMF / ethanol / water mixed solution;
[0048] S1.2: Dissolve 1 g of FeCl2·4H2O, 1.2 g of CoCl2·6H2O, 2.18 g of Ce(NO3)3·6H2O by mass, 2.15 g of Zr(NO3)4, and 0.64 g of terephthalic acid in the DMF / ethanol / water mixed solution, stir in a magnetic stirrer for 60 min, pour it into the inner liner of a polytetrafluoroethylene reaction kettle, seal the reaction kettle and place it in an oven at 135 °C for 12 h;
[0049] S1.3: After the reaction is completed, when the reaction kettle naturally cools to room temperature, take out the product in the inner liner, wash it 2 times with absolute ethanol and deionized water, and dry it at 100 °C for 4 h to obtain the Fe-Co-Ce-Zr four-metal MOFs material.
[0050] S2: Preparation of nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material
[0051] S2.1: Mix urea and the Fe-Co-Ce-Zr four-metal MOFs material synthesized in step S1 evenly in ultrapure water. The mass ratio of urea, Fe-Co-Ce-Zr four-metal MOFs material, and ultrapure water is 1:5:20, and stir at a speed of 50 r / min for 2 h to obtain a mixture;
[0052] S2.2: The mixture is filtered and rinsed in a 70 wt% ethanol solution, repeated 4 times, and then heated to 600 °C at a heating rate of 5 °C / min in an N2 atmosphere and carbonized at this temperature for 3 h. After the obtained powder is naturally cooled to room temperature, a nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material is obtained.
[0053] S3: Plasma treatment
[0054] The nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material is placed in a plasma reactor, with O2 / H2O as the working gas. The flow rate of O2 in the plasma reactor is 50 sccm, and the flow rate of H2O is 50 sccm. Under the conditions of a discharge frequency of 20 kHz, a discharge voltage of 15 kV, and a discharge time of 5 min, the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C is treated with plasma to obtain a nitrogen-doped four-metal MOFs-derived carbon composite material.
[0055] Example 3:
[0056] A preparation method of a nitrogen-doped four-metal MOFs-derived carbon composite material is as Figure 1 shown, including the following steps:
[0057] S1: Preparation of Fe-Co-Ce-Zr four-metal MOFs material
[0058] S1.1: 45 g of DMF, 10 g of absolute ethanol, and 10 g of water are stirred and mixed evenly to prepare a DMF / ethanol / water mixed solution;
[0059] S1.2: 1 g of FeCl2·4H2O, 1.2 g of CoCl2·6H2O, 2.18 g of Ce(NO3)3·6H2O by mass, 2.15 g of Zr(NO3)4, and 0.64 g of terephthalic acid are dissolved in the DMF / ethanol / water mixed solution, stirred in a magnetic stirrer for 60 min, poured into the inner liner of a polytetrafluoroethylene reaction kettle, and after the reaction kettle is sealed, it is placed in an oven at 135 °C for reaction for 12 h;
[0060] S1.3: After the reaction ends and the reaction kettle is naturally cooled to room temperature, the product in the inner liner is taken out, washed 2 times with absolute ethanol and deionized water, and dried at 100 °C for 4 h to obtain the Fe-Co-Ce-Zr four-metal MOFs material.
[0061] S2: Preparation of nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material
[0062] S2.1: Mix urea and the Fe-Co-Ce-Zr four-metal MOFs material synthesized in step S1 evenly in ultrapure water. The mass ratio of urea, Fe-Co-Ce-Zr four-metal MOFs material to ultrapure water is 1:5:20. Stir at a speed of 50 r / min for 2 h to obtain a mixture.
[0063] S2.2: Filter and rinse the mixture in a 70 wt% ethanol solution 4 times. Then, heat it to 700 °C at a heating rate of 5 °C / min in an N2 atmosphere and keep the temperature for carbonization for 3 h. After the obtained powder is naturally cooled to room temperature, a nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material is obtained.
[0064] S3: Plasma treatment
[0065] Place the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material in a plasma reactor. Use O2 / H2O as the working gas. The flow rate of O2 in the plasma reactor is 50 sccm, and the flow rate of H2O is 50 sccm. Under the conditions of a discharge frequency of 20 kHz, a discharge voltage of 15 kV, and a discharge time of 5 min, use plasma to treat the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C to obtain a nitrogen-doped four-metal MOFs-derived carbon composite material.
[0066] Example 3:
[0067] A preparation method of a nitrogen-doped four-metal MOFs-derived carbon composite material, as Figure 1 shown, includes the following steps:
[0068] S1: Preparation of Fe-Co-Ce-Zr four-metal MOFs material
[0069] S1.1: Stir and mix 45 g of DMF, 10 g of absolute ethanol, and 10 g of water evenly to prepare a DMF / ethanol / water mixed solution.
[0070] S1.2: Dissolve 1 g of FeCl2·4H2O, 1.2 g of CoCl2·6H2O, 2.18 g of Ce(NO3)3·6H2O in mass parts, 2.15 g of Zr(NO3)4, and 0.64 g of terephthalic acid in the DMF / ethanol / water mixed solution. Stir in a magnetic stirrer for 60 min, pour it into the inner liner of a polytetrafluoroethylene reaction kettle. After the reaction kettle is sealed, place it in an oven at 135 °C for reaction for 12 h.
[0071] S1.3: After the reaction ends, when the reaction kettle is naturally cooled to room temperature, take out the product in the inner liner, wash it 2 times with absolute ethanol and deionized water, and dry it at 100 °C for 4 h to obtain the Fe-Co-Ce-Zr four-metal MOFs material.
[0072] S2: Preparation of Nitrogen-doped Fe-Co-Ce-Zr Tetrametallic MOFs-C Material
[0073] S2.1: Mix urea and the Fe-Co-Ce-Zr tetrametallic MOFs material synthesized in step S1 evenly in ultrapure water. The mass ratio of urea, Fe-Co-Ce-Zr tetrametallic MOFs material, and ultrapure water is 1:5:20. Stir at a speed of 50 r / min for 2 h to obtain a mixture;
[0074] S2.2: Filter and rinse the mixture in a 70 wt% ethanol solution for 4 times. Then, heat it to 900 °C at a heating rate of 5 °C / min in an N2 atmosphere and keep the temperature for carbonization for 3 h. After the obtained powder is naturally cooled to room temperature, the nitrogen-doped Fe-Co-Ce-Zr tetrametallic MOFs-C material is obtained.
[0075] S3: Plasma Treatment
[0076] Place the nitrogen-doped Fe-Co-Ce-Zr tetrametallic MOFs-C material in a plasma reactor. Use O2 / H2O as the working gas. The flow rate of O2 in the plasma reactor is 50 sccm, and the flow rate of H2O is 50 sccm. Under the conditions of a discharge frequency of 20 kHz, a discharge voltage of 15 kV, and a discharge time of 5 min, use plasma to treat the nitrogen-doped Fe-Co-Ce-Zr tetrametallic MOFs-C to obtain a derivative carbon composite material of nitrogen-doped tetrametallic MOFs.
[0077] Comparative Example 1:
[0078] The difference between this comparative example and Example 1 is that no nitrogen source is added.
[0079] Comparative Example 2:
[0080] The difference between this comparative example and Example 1 is that carbonization is not carried out.
[0081] Use the composite materials prepared in Examples 1-4 and Comparative Examples 1 and 2 as samples for benzene and toluene gas adsorption tests: Use a UTEST static adsorption device to test the benzene and toluene gas adsorption of the materials. Control the test flow rate (10 L / min), test resistance (<80 pa), and test concentration (5 ppm). The test results are shown in Table 1, and the benzene cyclic adsorption capacity diagram is as Figure 2 shown.
[0082] Table 1
[0083]
[0084] As can be seen from Table 1, for the multi-metal MOFs-derived carbon materials prepared at the calcination temperatures in Examples 1-4, the initial efficiency and mass adsorption ratio for VOCs show a trend of first increasing and then decreasing. It can be seen that the optimal calcination temperature is 700 °C. At this time, the initial efficiency for toluene adsorption is 99.32%, and the mass adsorption ratio reaches 10.21%. The initial efficiency for benzene adsorption is 99.12%, and the mass adsorption ratio reaches 9.75%.
[0085] From Figure 2 it can be seen that after five cycles of benzene adsorption of the Fe-Co-Ce-Zr four-metal MOFs composite material treated by plasma, carbonized and nitrogen-doped, the adsorption capacity decays from 170 mg / g to 159 mg / g, indicating its excellent regenerative adsorption ability.
[0086] As Figures 3 - 4 shown, from Figure 3 the adsorption-desorption curve, it can be seen that the materials of Example 1, Comparative Example 1 and Comparative Example 2 all have micropore, mesopore and macropore filling. After calcination and plasma treatment, the specific surface area of the Fe-Co-Ce-Zr four-metal MOFs material is significantly increased, up to 4500 m2 / g, indicating that the Fe-Co-Ce-Zr four-metal MOFs-derived carbon material after plasma treatment has more active sites and a significant increase in the mass adsorption ratio for VOCs.
[0087] From Figure 4 it can be seen that the thermal stability of the Fe-Co-Ce-Zr four-metal MOFs material without calcination is 600 °C, the thermal stability of the Fe-Co-Ce-Zr four-metal MOFs-derived carbon material without nitrogen doping is 650 °C, while the thermal stability of the Fe-Co-Ce-Zr four-metal MOFs-derived carbon composite material after nitrogen doping is 700 °C, indicating that the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-derived carbon composite material has better thermal stability and is less likely to be affected by high-temperature environments and cause pore collapse, resulting in a decrease in adsorption performance.
[0088] The above embodiments are only illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Any person familiar with this technology can modify or change the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or changes completed by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.
Claims
1. A preparation method of a nitrogen-doped four-metal MOFs-derived carbon composite material, characterized in that, It includes the following steps: S1: Preparation of Fe-Co-Ce-Zr four-metal MOFs material S1.1: Mix DMF, absolute ethanol and water to make a DMF / ethanol / water mixed solution. Then dissolve FeCl2·4H2O, CoCl2·6H2O, Ce(NO3)3·6H2O, Zr(NO3)4 and terephthalic acid in the DMF / ethanol / water mixed solution. After stirring, pour it into a reaction kettle, seal the reaction. After the reaction is completed, when the reaction kettle cools naturally to room temperature, take out the product in the inner liner, wash and dry it to obtain the Fe-Co-Ce-Zr four-metal MOFs material; S2: Preparation of nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material Mix urea and the Fe-Co-Ce-Zr four-metal MOFs material synthesized in step S1 evenly in ultrapure water to obtain a mixture. Filter and rinse the mixture in an ethanol solution, and then heat and carbonize it in an N2 atmosphere. After the obtained powder cools naturally to room temperature, the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material is obtained; S3: Plasma treatment Place the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material in a plasma reactor, use O2 / H2O as the working gas, and under the conditions of a discharge frequency of 15 - 30 kHz, a discharge voltage of 15 - 20 kV, and a discharge time of 2 - 10 min, use plasma to treat the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C to obtain a derivative carbon composite material of nitrogen-doped four-metal MOFs.
2. The preparation method of a nitrogen-doped quadruple-metal MOFs-derived carbon composite material according to claim 1, wherein The preparation of the Fe-Co-Ce-Zr four-metal MOFs material in step S1 includes the following steps: S1.1: Stir and mix 32 - 45 parts by mass of DMF, 10 - 15 parts by mass of absolute ethanol and 10 - 15 parts by mass of water evenly to make a DMF / ethanol / water mixed solution; S1.2: Dissolve 1 - 1.2 parts by mass of FeCl2·4H2O, 1.2 - 2.2 parts by mass of CoCl2·6H2O, 2.1 - 2.5 parts by mass of Ce(NO3)3·6H2O, 2.15 - 2.6 parts by mass of Zr(NO3)4 and 0.6 - 0.8 parts by mass of terephthalic acid in the DMF / ethanol / water mixed solution, stir in a magnetic stirrer for 60 - 80 min, pour it into the inner liner of a polytetrafluoroethylene reaction kettle, seal the reaction kettle and place it in an oven at 125 - 150 °C for reaction for 10 - 12 h; S1.3: After the reaction is completed, when the reaction kettle cools naturally to room temperature, take out the product in the inner liner, wash it 2 - 3 times with absolute ethanol and deionized water, and dry it at 80 - 120 °C for 4 - 6 h to obtain the Fe-Co-Ce-Zr four-metal MOFs material.
3. The preparation method of a nitrogen-doped four-metal MOFs-derived carbon composite material according to claim 2, characterized in that, The preparation of the nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material in step S2 includes the following steps: S2.1: Mix urea and the Fe-Co-Ce-Zr four-metal MOFs material synthesized in step S1 evenly in ultrapure water. The mass ratio of urea, Fe-Co-Ce-Zr four-metal MOFs material, and ultrapure water is 1: (5 - 7):(15 - 30). Stir at a speed of 50 - 60 r / min for 2 - 3 h to obtain a mixture; S2.2: Filter and rinse the mixture in an ethanol solution, repeat 3 - 4 times, then heat it to 500 - 900 °C in an N2 atmosphere and keep the temperature for carbonization for 1 - 3 h. After the obtained powder is naturally cooled to room temperature, a nitrogen-doped Fe-Co-Ce-Zr four-metal MOFs-C material is obtained.
4. The preparation method of a nitrogen-doped quadruple-metal MOFs-derived carbon composite material according to claim 3, characterized in that, In step S2.2, the concentration of the ethanol solution is 70 - 95 wt%.
5. The preparation method of a nitrogen-doped four-metal MOFs-derived carbon composite material according to claim 3, characterized in that, In step S2.2, the heating rate of heating in an N2 atmosphere is 5 - 7 °C / min.
6. The preparation method of a nitrogen-doped four-metal MOFs-derived carbon composite material according to claim 1, characterized in that, In step S3, the flow rate of O2 in the plasma reactor is 50 - 500 sccm, and the flow rate of H2O is 10 - 100 sccm.
7. A nitrogen-doped derivative carbon composite material of four-metal MOFs, which is prepared by the preparation method of the nitrogen-doped derivative carbon composite material of four-metal MOFs according to any one of the above claims 1 - 6.
Citation Information
Patent Citations
Preparation method and application of aluminum-based metal organic skeleton@activated carbon composite material
CN109174019A
Graphene oxide modified activated carbon and preparation method thereof
CN109513422A